MANPOWER TRAINING AND EMPLOYEE DEVELOPMENT (CASE STUDY OF ACCESS BANK PLC, OBIOAKPOR LOCAL GOVERNMENT AREA PORT HARCOURT METROPOLIS RIVERS STATE) - Enyinna, Ugwu Kelechi; Chituo, Igbo Rita (Universitas Brawijaya, Indonesia, 2021)
This research examines the relationship between manpower training and employee development using a case study of Access Bank Plc in Obioakpor Local Government Area, Port Harcourt Metropolis Rivers State, Nigeria. A correlation survey design was adopted, data were sourced from 700 employees through a self-administered questionnaire, and the sample size was determined using the Taro Yamane method and calculated as 399. The judgmental non-probability sampling method was adopted in the distribution of the questionnaire. The correlation method was used to test the hypotheses to achieve the study objective. The findings revealed that job training has a significant positive relationship with employability skills, coaching has a significant positive relationship with employee competency. This study provides sufficient guidelines for human resources to integrate training programs into their mission statement to ensure employees are acquainted with job knowledge and skills. Future researchers are encouraged to explore this study using different industries and large sample sizes to generalize findings.